2011
DOI: 10.1021/ja205976v
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of O2 over N2 in a Redox–Active Metal–Organic Framework with Open Iron(II) Coordination Sites

Abstract: The air-free reaction between FeCl 2 and H 4 dobdc (dobdc 4À = 2,5-dioxido-1,4-benzenedicarboxylate) in a mixture of N,N-dimethylformamide (DMF) and methanol affords Fe 2 (dobdc) 3 4DMF, a metalÀorganic framework adopting the MOF-74 (or CPO-27) structure type. The desolvated form of this material displays a BrunauerÀEmmettÀTeller (BET) surface area of 1360 m 2 /g and features a hexagonal array of onedimensional channels lined with coordinatively unsaturated Fe II centers. Gas adsorption isotherms at 298 K indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
492
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 493 publications
(519 citation statements)
references
References 83 publications
26
492
1
Order By: Relevance
“…38 The nearest Fe···Fe distance of 3.04 Å in Fe 2 (dobdc), 28 which should match that in the isostructural Fe 2 (dobpdc), is the shortest of any metal−organic framework with infinite iron chains. Those that are the next closest are Fe III (gallate)·2H 2 O and Fe(bdc)(OH) 0.8 (F) 0.2 , possessing vertex-sharing octahedra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The nearest Fe···Fe distance of 3.04 Å in Fe 2 (dobdc), 28 which should match that in the isostructural Fe 2 (dobpdc), is the shortest of any metal−organic framework with infinite iron chains. Those that are the next closest are Fe III (gallate)·2H 2 O and Fe(bdc)(OH) 0.8 (F) 0.2 , possessing vertex-sharing octahedra.…”
Section: Resultsmentioning
confidence: 99%
“…21 The framework, shown in Figure 1a, has hexagonal channels with five-coordinate Fe 2+ ions lining the vertices in infinite 1D chains of edge-sharing square pyramids. 28 When solvated, the iron centers are pseudooctahedral. Similar phases are known to be redox-active and semiconducting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29 ] These open metal sites are shown to induce framework selectivity in the adsorption of small molecules and provide a mechanism for charge transfer on the framework surface. [30][31][32][33] While open metal sites provide strong interactions allowing gas adsorption at higher temperatures and lower pressures than typically used for energy-consuming cryodistillation processes, the adsorbate-adsorbent interactions are often weak relative to the formation of chemical bonds, providing facile release of the molecules during the regeneration step of a separation process. Recent work by McDonald and co-workers also revealed that certain diamines, grafted to open metal sites, can offer strong, selective binding of CO 2 at low pressures (ca.…”
Section: Mofs With Open Metal Coordination Sitesmentioning
confidence: 99%
“…One of the most well-studied MOFs to date is M 2 (dobdc), alternatively known as M-MOF-74 or CPO-27-M, where M = Mg, Mn, Fe, Co, Ni, Cu, or Zn ( Figure 2 ). [ 30,[37][38][39][40][41][42][43][44] The signifi cance of 2 H 6 ; the binding mechanisms (right) were unveiled by neutron powder diffraction. [ 30,31 ] The metal, carbon, oxygen, nitrogen, and deuterium atoms are drawn as orange, grey, red, royal blue, and light blue spheres, respectively.…”
Section: Mofs With Open Metal Coordination Sitesmentioning
confidence: 99%